2003
DOI: 10.1590/s0034-72992003000200002
|View full text |Cite
|
Sign up to set email alerts
|

O comportamento clínico e histológico da pele do rato submetida ao uso tópico e injetável de Mitomicina C

Abstract: The clinical and histological behavior of rat skin submitted to topical and injected Mitomycin C Resumo / SummaryObj etivo: A Mitomicina C é um quimioterápico que apresenta a capacidade de inibir fibroblastos in vitro. Esta característica a levou a ser usada experimentalmente em animais de laboratório e no ser humano, principalmente em oftalmologia, para inibir o processo cicatricial. Este trabalho visa acompanhar o processo de cicatrização de feridas cirúrgicas feitas em dorsos de ratos e tratadas topicamente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
4
4
0
1
Order By: Relevance
“…Afterwards it was equivalent to the mitomycin C control groups. Therefore we assume that mitomycin C may have slowed the occurrence of fibrosis on the applied area, which corroborate the results found by RIBEIRO et al (2003), who study the effects of mitomycin C in rat's derma. Regarding the immunohistochemical, the FGF-2 expressed for fibroblasts as well as for macrophages confirms the findings of FUNATO et al (1999) andWANG et al (2001).…”
Section: Discussionsupporting
confidence: 91%
“…Afterwards it was equivalent to the mitomycin C control groups. Therefore we assume that mitomycin C may have slowed the occurrence of fibrosis on the applied area, which corroborate the results found by RIBEIRO et al (2003), who study the effects of mitomycin C in rat's derma. Regarding the immunohistochemical, the FGF-2 expressed for fibroblasts as well as for macrophages confirms the findings of FUNATO et al (1999) andWANG et al (2001).…”
Section: Discussionsupporting
confidence: 91%
“…The adopted topical concentration was based in the values reported in the literature 10,13 . A previous paper indicated that the injection concentration used in this study would not result in rat tissue necrosis 11 . Two rats in the control group died as they were being anesthetized.…”
Section: Methodsmentioning
confidence: 81%
“…Many papers have shown that topical mitomycin-C alone might fail to achieve the desired results 10 . Injections of the agent have therefore been added to strengthen its effectiveness and to further mitigate the occurrence of surgical fibrosis [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…This has been demonstrated in vitro and in vivo using the rat model. [6][7][8][9][10][11] MMC decreases fibrosis in wounds treated with its topical form. 7 When used topically, this agent appears to be well tolerated, with no apparent side effects when applied to skin-incision sites.…”
Section: Introductionmentioning
confidence: 99%